PENGARUH PERAN PIMPINAN DALAM MENINGKATKAN KINERJA PEGAWAI PADA BAGIAN BIRO UMUM KANTOR GUBERNUR MALUKU - Sarpa Salaputa; Evandro A W Manuputty; Kalsum Lussy (P3M Politeknik Negeri Ambon, 2023)
The influence of the rolein improving employee performance at the general bureau of the Maluku groveror office,under the guidance of the first thesis Evandro A.W manuputty,SE.MM and thesis supervisor II kalsum lussy. This study aims to determine the influence of leaders in improving employee performance. The method uses simple linier analysis. The sample in this study amounted to 50 respondents. Data collection using a questionnaire. The results of this study indicate that 1% increase in leadership value,the employee performance will increase by 0.602. the regression coefficient is positive,so it can be said that the direction of the leadership influence (variable X) on employee performance (Variabel Y) is positive. And based on the signicance value obtained from the table above, it can be concluded that the leadership variable (X) on employee performance (Y). Keywords : Leadership,Employee Prformance.